2016
DOI: 10.1103/physrevd.93.053016
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the nonstandard interaction parameters in long baseline neutrino experiments

Abstract: In this article we investigate the prospects for probing the strength of the possible non-standard neutrino interactions (NSI) in long baseline neutrino oscillation experiments. We find that these experiments are sensitive to NSI couplings down to the level of 0.01-0.1 depending on the oscillation channel and the baseline length, as well as on the detector's fiducial mass. We also investigate the interference of the leptonic CP angle δ CP with the constraining of the NSI couplings. It is found that the interfe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Studies of matter NSI at DUNE and T2HK can be found in refs. [18,[22][23][24][25][26][27][28]. Studies of NSI with a second detector in Korea, in addition to the Kamiokande detector, can be found in refs.…”
Section: Jhep01(2017)071mentioning
confidence: 99%
“…Studies of matter NSI at DUNE and T2HK can be found in refs. [18,[22][23][24][25][26][27][28]. Studies of NSI with a second detector in Korea, in addition to the Kamiokande detector, can be found in refs.…”
Section: Jhep01(2017)071mentioning
confidence: 99%
“…We restricted ourselves to a discussion of CP asymmetries using solely the probability for the electron appearance channel P µe and showed how NSI effects translate at the level of event rates. Since then there has been a lot of activity [29,[38][39][40][41][42] in this direction exploring effects due to propagation NSI at long baselines. In [38], the goal was to discuss possible improvement of bounds on the NSI parameters using different channels at long baseline experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [41] deals with constraining NSI parameters using long baseline experiments. Very recently, it has been suggested that the proposed MOMENT experiment due to its much smaller baseline may prove helpful in solving the degeneracies due to NSI leading to unambiguous determination of CP violation [42].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, considering the model independent approach, we have studied the effect of lepton flavor violating NSIs on physics potential of long-baseline experiments [54]. Moreover, the recent works on the effect of NSI on the measurements of various neutrino oscillation experiments can be found in [55][56][57][58][59][60][61][62][63]. Since we focus on model-dependent approach in this paper, we consider the LVF decays of B meson in Z model to get the bound on NSI parameter as discussed in Sect.…”
Section: Neutrino Oscillation In the Presence Of Nsismentioning
confidence: 99%